Avaliação do efeito antibacteriano da medicação intracanal à base de hidróxido de cálcio associado ou não à clorexidina 1% no tratamento de dentes necrosados após trauma - Campos, Mirela Andrade (2010)
The goals of this dissertation are study of sodium hypochlorite and chlorhexidine as irrigants, through a literature review, evaluate and quantify, by means of bacterial culture, the antibacterial effect of biomechanical preparation and pulp-based hydroxide calcium with or without 1% chlorhexidine on bacteria in root canals of permanent teeth after necrotic injury, as well as verifying the presence of microorganisms Fusobacterium nucleatum and Black Pigmented Bacillus in these teeth. The sample consisted of 13 teeth, totaling 11 patients. Microbiological samples were taken after the coronal opening (A1), after root canal preparation (A2), followed by the use of intracanal dressing (A3) and 72 hours of the removal of the medication (A4). The samples were collected sequentially introducing three sterile absorbent paper cones inside the root canal for one minute. In A1, 100% of samples were positive, and the average colony forming units (CFU) of 7.7 x 104. In the second collection (A2), 5 / 13 samples were positive, with an average of 1.7 x 103 CFUs. After use of the medication (A3), 4 / 13 samples were positive, averaging 3.3 x 103 CFUs. A4, 6 / 13 samples were positive, with an average of 1 x 104 CFUs. Between A1 x A2, A3 and A1 x A1 x A4, we observed a reduction of CFUs was statistically significant (p <0.001). We were unable to observe a statistically significant difference (p> 0.05) among the other samples. We conclude that chemo-mechanical performs its antibacterial function by significantly reducing the number of micro-organisms from the main channel, but calcium hydroxide and its association with chlorhexidine 1% had no statistically significant difference, having an antibacterial effect limited not being able to prevent bacterial growth after its use as an intracanal medication.